Hvorfor vokser steder? - Vareide, Knut (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2018)
"Why do some places grow while others are shrinking? What are the most important driving forces behind increases in the number of inhabitants and jobs? How can places affect their own growth? This book is written for those who want to understand how structural forces affect the development of their locale and how one can create growth through increased attractiveness. Most Norwegian municipalities, cities, regions and counties try to stimulate growth and development in their localities. They want growth in the population and more jobs. This book describes the main features of regional development in Norway since 2000. Telemark Research Institute has proposed a new model, the attractiveness model, to explain the growth and development of places. This book explains how this model works, how it is constructed and how it can be used to understand the forces behind regional development."